New Perspectives on Food Blanching - Richter Reis, Felipe (Springer International Publishing : Imprint: Springer, 2017)
This book provides information on the advances in blanching and its effect on food. The author presents the concepts involved in old and novel blanching processes, the typical effects of blanching and the studies on novel blanching technologies. .